Can pH and Water-to-Protein Ratio be Good Instruments to Evaluate the Abusive Water Added in Seafood by Phosphate Addition?. Issue 3 (16th March 2019) - Lemos, Lyzandra Laís De Almeida; Gonçalves, Alex Augusto
ABSTRACT: The aim of the present study was to evaluate the effect of the phosphates on tuna meat pH, and water-to-protein ratio. Tuna fillets were soaked in cold (5 °C) tripolyphosphate solution (STPP) and blend phosphate (CARNAL® 961) at 3, 5 and 10% for 30, 60 and 120 min. The control group was represented by cold distilled water. After soaking, the samples were drained, weighed, frozen, stored (-35 °C, for 15 days), thawed, drained, and grilled. After each step, samples were withdrawn for the following analysis: pH, phosphate (as P2O5), moisture and protein. A gradual increase in pH and residual phosphate was observed, which remained below the limits established by national (for pH) and international (for phosphate) legislation. A moderate positive correlation between pH and phosphate values was observed. An increase in moisture content and the water-to-protein ratio were observed, and still below to the legislation limit (i.e., 6.0). We suggest a critical review and possible changes in the parameters which are used as indicators of abusive use of the phosphate additive in seafood to combat the economic fraud in the frozen seafood products. It should be emphasized that these suggestions should be the focus of the collaborative study for its validation.